EDUCATION AND ASSISTANCE IN PREPARING MSME FINANCIAL STATEMENTS FOR ACCESS TO FINANCING - Rita J D Atarwaman; Riska Tuguis; Nahda Latulumamina; Yoas Ongen Lawery; Irfan Fokatea (PT. Jurnal Center Indonesia Publisher, 2026)
Micro, Small, and Medium Enterprises (MSMEs) play an important role in the national economy but still face challenges in accessing financing from formal financial institutions. One of the main obstacles to financing access is the limited ability of MSME owners to prepare systematic, accurate, and standardized financial statements. Many MSMEs do not maintain proper transaction records, mix personal and business finances, and lack formal financial reports required for financing applications.This community service program aims to provide education and mentoring on simple financial statement preparation to improve financial literacy and financing readiness of MSMEs. The activities were carried out through socialization, basic accounting training, intensive mentoring on transaction recording, preparation of financial statements, and financing application simulations. The program was conducted for one month targeting Warung Rindu Malam MSME located in Poka Village, Ambon City.The results indicate an improvement in participants’ understanding and skills in financial recording and preparation of income statements, simple balance sheets, and cash flow statements. The targeted MSME successfully produced organized financial documents that are ready to be used for financing applications. This program is expected to encourage more professional and sustainable MSME financial management.